Jacques Rancière and the politics of art cinema - Harvey, James, 1987- (Edinburgh University Press, 2018)
Drawing on case studies of films including Charlie Kaufman's Synecdoche, New York, Nuri Bilge Ceylan's Climates and John Akomfrah's The Nine Muses, this books asks to what extent is politics shaping art cinema? And, in turn, could art cinema possibly affect the political structure of the world as we know it?